2005
DOI: 10.1080/15275920500351825
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Anthropogenic Stress in an Ecosystem: 3. Mesoscale Variability and Biotic Indices

Abstract: Previous work in the Ria Formosa Lagoon has revealed that it is possible to use macrofauna community structure as an indicator of contamination effects. Communities at sites adjacent to sewage outfalls indicated contamination but no pollution gradients were observed. In this study, macrofauna within a sub-section of the earlier work were investigated to determine the extent of mesoscale (10-100 m) variability and new indices of biological community structure. The results were evaluated using univariate (Marine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…AMBI has been validated using many different anthropogenic pressures on a world-wide basis (e.g. Borja et al 2003a;Chenery & Mudge 2005;Muxika et al 2005;Muniz et al 2005;Carvalho et al 2006;Quintino et al 2006;Fleischer et al 2007). Following these investigations, AMBI has been found to respond to different pressures, such as hypoxia and eutrophication processes, oil platform discharges, engineering works, dredging and fish aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…AMBI has been validated using many different anthropogenic pressures on a world-wide basis (e.g. Borja et al 2003a;Chenery & Mudge 2005;Muxika et al 2005;Muniz et al 2005;Carvalho et al 2006;Quintino et al 2006;Fleischer et al 2007). Following these investigations, AMBI has been found to respond to different pressures, such as hypoxia and eutrophication processes, oil platform discharges, engineering works, dredging and fish aquaculture.…”
Section: Introductionmentioning
confidence: 99%
“…Borja et al, 2003;Solís-Weiss et al, 2004;Chenery & Mudge, 2005;Muniz et al, 2005;Muxika et al, 2005;Carvalho et al, 2006;Quintino et al, 2006;Fleischer et al, 2007;Cheung et al, 2008). Following these investigations, AMBI has been found to respond to different drivers and pressures, such as: hypoxia and eutrophication processes; oil platform discharges; engineering works; dredging; fish aquaculture; etc.…”
Section: Validation Of Methodologiesmentioning
confidence: 97%
“…The distribution of sewage-derived compounds has previously been determined in this area; Mudge and Duce (2005) identified sources, sinks, and pathways of contaminants with lipid biomarkers whilst Hewitt and Mudge (2004), Hopkins and Mudge (2004), and Chenery and Mudge (2005) identified the presence of sewage contaminants with biological indicators. It is possible to separate sewage, marine, and terrestrial inputs with biomarkers, and to determine their relative influence at each site.…”
Section: Lipidsmentioning
confidence: 99%
“…Numerous studies have been undertaken within the Ria Formosa investigating water quality with the aid of biological indicators (Hewitt and Mudge, 2004;Hopkins and Mudge, 2004;Chenery and, Mudge, 2005), lipid analysis (Mudge and Duce, 2005) and oxygen concentrations (Mudge et al 2008); however, there is little information available regarding the biologically important nutrients (Newton and Mudge, 2005). These studies have determined the origin of contaminants and shown that both the Ramalhete Channel and the Esteiro de Maria Nova could be major contributors.…”
Section: Introductionmentioning
confidence: 98%